2019
DOI: 10.1111/1742-6723.13351
|View full text |Cite
|
Sign up to set email alerts
|

Clinical clearance and imaging for possible cervical spine injury in children in the emergency department: A retrospective cohort study

Abstract: Objectives While cervical spine injuries (CSIs) are rare in the paediatric population, presentations to EDs with possible neck injuries are common. Based on a lack of Australian data we set out to determine how many possible injuries are clinically cleared, what imaging is used on the remainder and the incidence and characteristics of confirmed paediatric CSIs. Methods We undertook a retrospective electronic medical record review of children <18 years with potential CSIs at a large tertiary paediatric trauma c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…These data correspond with the findings of previous studies-performed both in level 1 trauma centres and other hospitals-which have also reported low incidences. The incidence varies from 0.3-3.7%, depending on the specific population studied [4][5][6][7]28]. Our study confirms that a child presenting at a level 2 trauma centre after blunt trauma is very unlikely to have relevant C-spine injury.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…These data correspond with the findings of previous studies-performed both in level 1 trauma centres and other hospitals-which have also reported low incidences. The incidence varies from 0.3-3.7%, depending on the specific population studied [4][5][6][7]28]. Our study confirms that a child presenting at a level 2 trauma centre after blunt trauma is very unlikely to have relevant C-spine injury.…”
Section: Discussionsupporting
confidence: 69%
“…In the paediatric ED, a CT of the brain is by far the most commonly performed CT examination; the largest increase, however, has been reported for CT scans of the cervical spine and chest [32,33]. And although some studies report that the total volume of CT utilization in children seems to have declined over the last decade-possibly due to the widespread introduction of clinical decision tools [26,31,34]-others still report a stable, increased or unexpectedly high CT utilization rate in children suffering blunt trauma [28,35]. This suggests that protocols are still not being sufficiently implemented in daily practice, or that concurrent developments are hindering physicians' adherence to these protocols.…”
Section: Discussionmentioning
confidence: 99%